Comparing the Effectiveness of the Triple P-Positive Parenting Program and Parenting Program of Acceptance and Commitment Therapy on Parent-Child Relationship and Self-efficacy of Mothers With Oppositional Defiant Disorder Children - Shahriar Amini Naghani; Samaneh Najarpourian; Seyaed Abdolvahhab Samavi (Gonabad University of Medical Sciences, 2020)
Background: Parents may face challenges in establishing relationships with their children with Oppositional Defiant Disorder (ODD). This research was conducted to compare the effectiveness of the Triple P-Positive Parenting Program (Triple P) and the Acceptance and Commitment Therapy (ACT)-based parenting on the parent-child relationship and parental self-efficacy of parents with ODD children.  Methods: The design of this research was quasi-experimental and included two intervention groups and one control group. The study population consisted of all mothers of first-, second-, and third-grade primary school children with ODD who lived in Shahrekord City, Iran in 2018. The study mothers were chosen by purposive sampling method and then divided into three groups of Triple P, ACT, and control. Data were gathered using the Oppositional Defiant Disorder Rating Scale (ODDRS), the Parent-Child Relationship Scale (PCRS) and the Parental Self-Efficacy Questionnaire (PSEQ). Data analyses were carried out using multivariate analysis of variance, repeated measures analysis of variance and post hoc Bonferroni test in SPSS.  Results: Significant differences in the Post-test parent-child relationship (F=4.53, P<0.05) and follow-up parent-child relationship (F=8.03, P<0.05) and Post-test parental self-efficacy (F=11.24, P<0.05) and follow-up parental self-efficacy (F=11.04, P<0.05) were observed among Triple P, ACT, and control group. The findings also showed no significant difference in post-test and follow-up phases (P>0.05) between Triple P and ACT groups. There were significant differences in parent-child relationships and parental self-efficacy between Pre-test and Post-test phases in Triple P and ACT (P<0.05) groups, but there was no significant difference between the Post-test and follow-up stages (P>0.05).  Conclusion: The results of this research suggest that Triple P and ACT are effective techniques for improving parent-child relationships and parental self-efficacy in mothers of children with ODD.